Genetic and epigenetic interactions in adaptive thermogenesis pathways in association with obesity from a Public Health Genomics perspective (Italian Journal of Public Health, 2012)
Background: studying and apprehending the pathways and mechanisms by which overweight and obesity trigger complex disease progression is of prime importance for the development of therapy and prevention measures of this major public health burden. This review describes Single Nucleotide Polymorphisms (SNPs) and epigenetic methylation as well as histone modification in genes with relevance in adaptive thermogenesis and their possible role in the development of obesity. Epigenetic marks are discussed as solid biomarkers for gene-environment interactions.Methods: a PubMed search on genetic and epigenetic variation of genes involved in adaptive thermogenesis was performed. The search included English publications between December 1996 and July 2010 reporting associations between SNPs and obesity in Caucasians. The search on epigenetic regulation was limited to DNA methylation and histone modifications. Genes that were found to be associated with the adaptive thermogenesis pathway included beta-3 adrenergic receptor (ADRB3), uncoupling protein 1 (UCP1), the transcription factors peroxisome proliferated activator receptor gamma (PPARγ), peroxisome proliferated activator receptor gamma co-activator 1 alpha (PGC1α), retinoid acid X receptor alpha (RXRα), CCAAT/enhancer-binding protein alpha (C/EBPα), fatty acid binding protein 4 (FABP4) and lipoprotein lipase (LPL).Results: epigenetic studies are mainly discovery orientated and do not test hypotheses. However, SNPs as well as epigenetic mechanisms seem to regulate obesity and adaptive thermogenesis whereas genetic association studies are inconsistent.Conclusions: the aim of this work was to confirm evidences on the contribution of genetic variations as well as epigenetic regulatory mechanisms of genes associated to obesity. The integration of epigenetic markers in epidemiologic research could help to unravel multi gene-environment interactions.With this article we show the importance to introduce aspects of the epigenetic regulation in the assessment of obesity: We also discuss the benefits of including epigenomics as an integrative way to account for an individual’s environmental impact in public health policies.